Peningkatan Kompetensi Komunitas Wanita Pemilik Usaha Kecil Menengah melalui Workshop Public Speaking - Agus Purbathin Hadi; Shinta Desiyana Fajarica; Tenri Waru; Novita Maulida (Jurnal Nomosleca, 2020)
Communication is an important aspect of life to interact with each other. Public speaking is one part of communication activities. Public Speaking, which used to be known as rhetoric, is now a major need for humans, because communication needs are becoming increasingly significant and crucial that penetrate into various aspects of life. Public speaking later became one of the disciplines of public communication. With the development of such public speaking as a public communication skill that must be possessed by anyone if they want to be successful in the economic, social, political and even cultural fields, because human communication on earth is almost 99% done verbally. Women Community Small Medium Business Owners are a group of women who are in one community to develop the potential of each individual. The output to be achieved is the increase in knowledge, skills and skills in communication in both formal and informal forums. Public speaking is not an easy task. Need good language skills. Fear and anxiety become a big problem, especially for beginners who have no experience in public speaking. This also happened to women community members who owned small and medium businesses in Rarang village, Terara sub-district, East Lombok Regency. Their language competence is inadequate. That is why Public Speaking training activities are held. This activity is expected to improve their language skills. By using the training method obtained satisfactory results. The enthusiasm and positive response of the participants showed that the training activities were indeed needed to increase the potential of the speaking ability of the community of women who owned small and medium businesses in Rarang Village. In addition, using this approach can certainly increase the participation of women in more formal public forums. Increasing the role of women will certainly also affect the capacity and capabilities of women in their involvement in public forums.Keywords: Communication, Public Speaking, Business Community, WomanDOI: https://doi.org/10.26905/nomosleca.v6i1.3959